Establishment of OPG Transgenic Mice and the Effect of OPG on Bone Microarchitecture. (27th March 2013) - Wu, Ying; Liu, Jianghua; Guo, Hui; Luo, Qiong; Yu, Ziying; Liao, Eryuan; Zu, Xuyu
Abstract : Osteoprotegerin (OPG) plays a determinant role in regulating bone metabolism, but the effect of OPG on bone microarchitecture needs to be further elucidated. We attempted to construct pCI-hOPGp-mOPG vector containing human OPG promoter and FLAG tag and to microinject vector into fertilized zygotes from C57BL/6J × CBA mice to prepare transgenic mice. The OPG transgenic positive mice were identified by PCR and western blotting. Twelve-week-old OPG transgenic mice (OPG-Tg mice) and wild-type mice (WT mice) were utilized in the study of bone microarchitecture. Microcomputed tomography (micro-CT) data showed that compared with WT mice, the tibia of OPG-Tg mice showed an increased volumetric BMD (vBMD), tissue BMD (tBMD), trabecular thickness (Tb.Th), and trabecular number (Tb.N), and a decreased trabecular separation (Th.Sp) (P < 0.05 ) . The cortical bone microarchitecture parameters, such as cortical area (Ct.Ar), cortical thickness (Ct.Th), cortical BMD (Ct.BMD), cortical BMC (Ct.BMC), BMD, and BMC of femur, were increased, and the inner perimeter (In.Pm) was decreased, in OPG-Tg mice, compared to those in WT mice (P < 0.05 ). The established OPG transgenic mouse model could be valuable for further studying the biological significance and gene regulation of OPG in vivo.